In nivo and in vitro study of the effect of cardiovascular stenting in hematological, hemorheological and hemodynamic parameters - Kokkinidou, Despoina (My University, 2025)
Background: Coronary artery disease is the most common type of heart disease and cause of death worldwide. Specifically, the developing plaque formation narrows the passage of the coronary arteries, leading to a decreased supply of blood, oxygen, and other vital nutrients to the heart. Cardiovascular implantation (stent) has been used as the primary solution in restoring blood flow after arterial stenosis. Despite the wide clinical usage of stents, stent functionality is compromised by complications at the site of implantation, including thrombosis and occlusion. The usage of stenting alters the local flow conditions in the artery, and the effects of these alterations on stent thrombosis and restenosis are still not fully understood. Furthermore, there is limited information on the effect of the stent presence on specific hemorheological parameters. Objective: This study aims to investigate the effects of stent implantation on hematological, hemorheological, and hemodynamic parameters, assessing how these alterations may compromise stent functionality and circulatory physiology. Methods: Experimental evaluations were conducted using both in vivo and in vitro approaches. In vivo experiments involved implanting custom-made self-expanding nitinol stents in the common carotid artery of male mice (CD1), with blood samples collected at 5- and 10-weeks post-implantation for hematological and hemorheological analysis. In vitro studies involved blood flow through single and overlapping stents within polymer tubes under different flow conditions and configurations, reflecting coronary artery morphologies. Commercially available stents were placed in clear perfluoroalkoxy alkane tubing connected to a syringe-pump and pressure sensing system. Hematological and hemorheological measurements, were performed using standard techniques. Results: Stent implantation led into notable changes in hematological and hemorheological indices. Results from the In vivo studies demonstrated increased hematocrit and decreased RBC deformability at 10 weeks post-implantation, contributing to elevated blood viscosity, despite a slight reduction in RBC aggregation. These alterations may be linked to inflammatory responses at the implant site. Findings from the in vitro investigation revealed a significant increase in RBC aggregation, particularly among female subjects, and altered blood viscosity at higher flow rates. The influence of stenting on the in vitro hemodynamics was revealed in the pressure-drop across the stented region, which was found to vary, depending on the stent configuration. Conclusions: The presence of a stent influences specific hematological, hemorheological and hemodynamic parameters, at specific flow conditions, potentially impacting long-term stent functionality. The findings underscore the need for further investigation into the physiological consequences of stent-induced hemorheological changes to optimize stent design and improve clinical outcomes.
Keywords: coronary artery disease; stent; blood; hematology; hemorheology